Finding a predictive value for the degree of pain for partial rupture of the anterior cruciate ligament in terms of some indicators of the functional structure of the knee joint for injured athletes - Ammar Mzial Shnta; Amaar Shanta (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Understanding the relationship between the functional structure of the knee and pain can contribute to increasing the therapist’s knowledge of the degree of pain and improving the quality of rehabilitation programs for injured athletes.